Aqueous cutting fluid composition and aqueous cutting fluid
By using water-based cutting fluid compositions with components such as acrylic copolymers in the water-based cutting fluid, the problem of degradation of lubrication performance of traditional water-based cutting fluid under high temperature, high pressure and high shear conditions is solved, and excellent lubricating performance, rust resistance and viscosity shear stability are achieved.
Patent Information
- Application Number
- CN202510223765.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-04-15
AI Technical Summary
Traditional water-based cutting fluid is prone to viscosity drop or stratification under high temperature, high pressure and high shear conditions, resulting in a decrease in lubricating performance and affecting the continuity and stability of the processing process.
A water-based cutting fluid composition is used, which contains acrylic copolymer, surfactant, vinyl coupling agent modified anti-wear lubricant, extreme pressure agent, bactericide, polyol solvent and water. Through the synergistic action of these components, a stable lubricating film is formed, and the lubricating performance and shear stability of the cutting fluid are improved.
Significantly reduces friction coefficient, improves anti-rust performance, enhances viscosity and shear stability, ensures the continuity and stability of the processing process, extends tool life, and is suitable for metal processing in high humidity environments.
Smart Images

Figure BDA0005289518710000021 
Figure FDA0005289518700000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cutting fluids, and in particular relates to an aqueous cutting fluid composition and an aqueous cutting fluid. Background Art
[0002] With the rapid development of modern manufacturing industry, metal processing technology has increasingly higher requirements for cutting fluids. As an indispensable auxiliary material in the metal processing process, cutting fluids not only need to have good lubricity and cooling performance, but also need to have excellent rust resistance, stability and environmental protection. Traditional cutting fluids are mainly divided into oil-based cutting fluids and water-based cutting fluids. Although oil-based cutting fluids have excellent lubrication properties, they are flammable, pollute the environment, and are difficult to clean. Although water-based cutting fluids are more environmentally friendly, their lubricity and rust resistance are often not as good as oil-based cutting fluids, and they are prone to breed bacteria at high temperatures, resulting in a short service life.
[0003] At present, in order to improve the rust resistance of water-based cutting fluids, rust inhibitors are often added to water-based cutting fluids. However, the rust inhibitors currently added are easy to decompose under high temperature and high pressure conditions, resulting in performance degradation. Under high shear conditions, traditional cutting fluids are prone to viscosity loss or stratification, resulting in reduced lubrication performance and affecting the continuity and stability of the processing process. Summary of the invention
[0004] The first aspect of the present invention provides an aqueous cutting fluid composition, which contains, by weight: 5-20 parts of acrylic copolymer, 1-5 parts of surfactant, 10-25 parts of vinyl coupling agent modified anti-wear lubricant, 1-5 parts of extreme pressure agent, 0.1-2 parts of bactericide, 10-30 parts of polyol solvent, and 40-80 parts of water.
[0005] In the present invention, the aqueous cutting fluid containing the aqueous cutting fluid composition of the present invention can form a stable lubricating film on the metal surface, significantly reduce the friction coefficient, and has excellent rust prevention performance without adding a rust inhibitor, and also has excellent shear stability.
[0006] As a preferred technical solution of the present invention, the aqueous cutting fluid composition contains, by weight: 10-15 parts of acrylic copolymer, 2.5-3 parts of surfactant, 12-15 parts of vinyl coupling agent modified anti-wear lubricant, 2.5-3 parts of extreme pressure agent, 0.3-0.5 parts of bactericide, 15-20 parts of polyol solvent, and 65-70 parts of water.
[0007] Acrylic acid copolymer is a kind of high molecular compound generated by copolymerization of acrylic acid and other monomers. As a preferred technical solution of the present invention, the acrylic acid copolymer contains a structural unit A provided by acrylic acid and a structural unit B provided by a vinyl imidazole compound represented by formula (I).
[0008]
[0009] In formula (I), R1 is selected from C1-C12 alkyl, X - It is an anion.
[0010] In the present invention, it is found that when the polypropylene copolymer contains structural unit B, the aqueous cutting fluid composition not only has excellent lubrication performance, but also has excellent shear stability. It is speculated that this is because the imidazole cation in the structural unit B can form a steric hindrance in the system, restricting the free movement of the chain segments, thereby reducing the chain orientation during the shear process. At the same time, the vinyl imidazole compound has high thermal stability, which enhances the thermal conductivity of the acrylic copolymer, can quickly disperse the heat generated during the shear process, and prevent the viscosity from decreasing due to local overheating.
[0011] The alkyl group in the C1-C12 alkyl group in formula (I) of the present invention may be a straight-chain alkyl group or a branched-chain alkyl group. The C1-C12 alkyl group in the present invention refers to a straight-chain alkyl group unless otherwise specified.
[0012] In formula (I) of the present invention, the types of C1-C12 alkyl groups that can be listed include methyl, ethyl, butyl, hexyl, octyl, etc. As a preferred technical solution of the present invention, in formula (I), R1 is selected from C4-C6 alkyl groups.
[0013] In the present invention, the aqueous cutting fluid composition obtained by controlling the carbon number of the alkyl group of R1 within the above range has better comprehensive performance.
[0014] As a preferred technical solution of the present invention, in formula (I), X - It is tetrafluoroborate ion, iodide ion, bromide ion or acid radical ion.
[0015] As a more preferred technical solution of the present invention, in formula (I), X - It is the tetrafluoroborate ion.
[0016] In the present invention, it is found that when X - The composition has better rust resistance due to the tetrafluoroborate ion. It is presumed that this is because the acrylic copolymer has better interfacial wettability and better film formation. At the same time, the tetrafluoroborate ion has strong electronegativity and can electrostatically adsorb to the positively charged area on the metal surface, further enhancing the stability of the protective film.
[0017] As a preferred technical solution of the present invention, the molar ratio of the structural unit A to the structural unit B is 1:(0.1-1), for example, 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9 or 1:1, preferably 1:(0.3-0.4).
[0018] The molar ratio of the structural unit A to the structural unit B in the present invention is based on the acrylic acid and the vinyl imidazole compound in the preparation of the acrylic copolymer.
[0019] The acrylic copolymer in which the ratio of the structural unit A to the structural unit B is controlled within the above range enables the composition of the present invention to have better shear stability.
[0020] The acrylic copolymer of the present invention can be prepared by any copolymerization method in the art. As a preferred technical solution of the present invention, the preparation method of the acrylic copolymer comprises: in the presence of an initiator and a solvent, acrylic acid and a vinyl imidazole compound represented by formula (I) are copolymerized, and then the solvent is removed.
[0021] As a preferred technical solution of the present invention, the initiator is selected from azo initiators, such as azobisisobutyronitrile.
[0022] As a preferred technical solution of the present invention, the mass of the initiator is 0.1-0.2 wt % of the total mass of acrylic acid and the vinyl imidazole compound represented by formula (I).
[0023] As a preferred technical solution of the present invention, the solvent is selected from at least one of benzene, toluene and chlorobenzene, preferably chlorobenzene.
[0024] As a preferred technical solution of the present invention, the mass of the solvent is 2-4 times the total mass of the acrylic acid and the vinyl imidazole compound represented by formula (I).
[0025] As a preferred technical solution of the present invention, the copolymerization reaction conditions include: being carried out in a nitrogen atmosphere; the temperature is 60-80° C.; and the time is 2-2.5 hours.
[0026] In the present invention, the method for removing the solvent may be a conventional method in the art, such as a distillation method, and the present invention will not elaborate on this.
[0027] As a preferred technical solution of the present invention, the surfactant is selected from a nonionic surfactant, preferably the nonionic surfactant is selected from at least one of propylene glycol block polyether Pluronic L31, propylene glycol block polyether Pluronic L35, propylene glycol block polyether Pluronic L61, propylene glycol block polyether Pluronic L62, propylene glycol block polyether Pluronic L64 and propylene glycol block polyether Pluronic L81, preferably selected from propylene glycol block polyether Pluronic L61 and / or propylene glycol block polyether Pluronic L62.
[0028] In the present invention, it is found that the synergistic effect of anionic surfactant and acrylic acid copolymer can form a stable lubricating film on the metal surface, thereby improving the lubricating performance of the cutting fluid composition.
[0029] As a preferred technical solution of the present invention, the preparation method of the vinyl coupling agent modified anti-wear lubricant includes: mixing graphene with ethanol, then adding the vinyl coupling agent for reflux reaction, and then performing solid-liquid separation and solid-phase drying.
[0030] The graphene in the present invention may be conventional graphene powder in the art, which can be obtained commercially, such as KNG-G2 graphene powder purchased from Xiamen Kaina Graphene Technology Co., Ltd.
[0031] As a preferred technical solution of the present invention, the vinyl coupling agent is selected from vinyl triisopropoxy titanate and / or vinyl tri(dioctyl pyrophosphate) titanate, preferably vinyl triisopropoxy titanate.
[0032] As a preferred technical solution of the present invention, the mass ratio of the vinyl coupling agent to graphene is (0.04-0.06):1.
[0033] As a preferred technical solution of the present invention, the mass of the ethanol is 3-5 times the mass of the graphene.
[0034] As a preferred technical solution of the present invention, the conditions of the reflux reaction include: temperature of 50-70° C. and time of 2-4 hours.
[0035] The conditions for solid phase drying in the present invention are not particularly limited, and for example, drying is performed at 90-100° C. for 6-12 hours.
[0036] As a preferred technical solution of the present invention, the extreme pressure agent is selected from sulfided fatty acid esters and / or phosphate compounds, preferably sulfided fatty acid esters.
[0037] As a preferred technical solution of the present invention, the sulfurized fatty acid ester is at least one selected from dimethyl dithiocarboxylate, distearyl thiodipropionate and sulfurized fatty acid methyl ester, preferably dimethyl dithiocarboxylate.
[0038] As a preferred technical solution of the present invention, the fungicide is selected from isothiazolinone compounds.
[0039] The isothiazolinone compounds that can be cited in the present invention include at least one of isothiazolinone, 5-chloro-2-methyl-4-isothiazoline-3-one, 2-methyl-4-isothiazoline-3-one, 2-octyl-4-isothiazoline-3-one and 5-chloro-2-methyl-4-isothiazoline-3-one.
[0040] As a preferred technical solution of the present invention, the polyol solvent is selected from at least one of ethylene glycol, diethylene glycol, propylene glycol, 1,3-propylene glycol, 1,4-butanediol and 1,2-butanediol, preferably propylene glycol.
[0041] A second aspect of the present invention provides an aqueous cutting fluid, wherein the aqueous cutting fluid comprises the aqueous cutting fluid composition described in the first aspect of the present invention.
[0042] The aqueous cutting fluid of the present invention can be obtained by mixing the various components in the aqueous cutting fluid composition, and the mixing conditions can be: stirring at room temperature and a rotation speed of 1200-2000 r / min for 30-60 minutes.
[0043] Compared with the prior art, the present invention has at least the following beneficial effects:
[0044] 1. The water-based cutting fluid of the present invention uses water as the main component, which reduces the use of mineral oil and organic solvents and reduces the risk of environmental pollution;
[0045] 2. The cutting fluid of the present invention has better lubrication performance, can effectively reduce tool wear, extend tool life, and improve the finish of the processed surface;
[0046] 3. The anti-rust performance of the cutting fluid of the present invention is more durable, which can meet the needs of long-term processing and storage, and is particularly suitable for metal processing in high humidity environments;
[0047] 4. Many cutting fluids are prone to viscosity drop or stratification under high-speed shear conditions, affecting the processing effect. The synergistic effect of the various components in the cutting fluid composition of the present invention significantly improves the viscosity shear stability and ensures the continuity and stability of the processing process. DETAILED DESCRIPTION
[0048] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] Example 1
[0050] Preparation of acrylic acid copolymer:
[0051] Chlorobenzene and azobisisobutyronitrile were added into a reactor, and then acrylic acid and 1-vinyl-3-butyl imidazole tetrafluoroborate were added in a molar ratio of 1:0.4, and then the air in the reactor was replaced by nitrogen for 30 minutes, and then the reaction system was heated to 80°C, reacted for 2 hours, cooled to room temperature, and the reaction solution was distilled to remove chlorobenzene to obtain an acrylic acid copolymer;
[0052] The mass of chlorobenzene is 3 times the total mass of acrylic acid and 1-vinyl-3-butyl imidazole tetrafluoroborate; the mass of azobisisobutyronitrile is 0.1wt% of the total mass of acrylic acid and 1-vinyl-3-butyl imidazole tetrafluoroborate.
[0053] Preparation of vinyl coupling agent modified anti-wear lubricant:
[0054] Graphene (KNG-G2 graphene powder purchased from Xiamen Kaina Graphene Technology Co., Ltd.) was mixed with ethanol, and then vinyl triisopropoxy titanate was added to reflux at 70°C for 2 hours, followed by solid-liquid separation and solid phase drying at 90°C for 8 hours;
[0055] Among them, the mass ratio of vinyl triisopropoxy titanate to graphene is 0.06:1; the mass of ethanol is 3 times the mass of graphene.
[0056] Preparation of water-based cutting fluid:
[0057] Prepare the following components by weight: 15 parts of the acrylic copolymer prepared above, 2.5 parts of propylene glycol block polyether Pluronic L61, 15 parts of the vinyl coupling agent modified anti-wear lubricant prepared above, 2.5 parts of dimethyl dithiocarboxylate, 0.5 parts of 5-chloro-2-methyl-4-isothiazoline-3-one, 20 parts of propylene glycol, and 70 parts of water;
[0058] The above components were stirred at room temperature and a rotation speed of 1600 r / min for 40 minutes to obtain an aqueous cutting fluid.
[0059] Example 2
[0060] Preparation of acrylic acid copolymer:
[0061] Chlorobenzene and azobisisobutyronitrile were added into a reactor, and then acrylic acid and 1-vinyl-3-hexyl imidazole tetrafluoroborate were added in a molar ratio of 1:0.35, and then the air in the reactor was replaced by nitrogen for 30 minutes, and then the reaction system was heated to 75°C, reacted for 2.5 hours, cooled to room temperature, and the reaction solution was distilled to remove chlorobenzene to obtain an acrylic acid copolymer;
[0062] The mass of chlorobenzene is 3 times the total mass of acrylic acid and 1-vinyl-3-hexyl imidazolium tetrafluoroborate; the mass of azobisisobutyronitrile is 0.1wt% of the total mass of acrylic acid and 1-vinyl-3-hexyl imidazolium tetrafluoroborate.
[0063] Preparation of vinyl coupling agent modified anti-wear lubricant:
[0064] Graphene (KNG-G2 graphene powder purchased from Xiamen Kaina Graphene Technology Co., Ltd.) was mixed with ethanol, and then vinyl triisopropoxy titanate was added to reflux at 60°C for 3 hours, followed by solid-liquid separation and solid phase drying at 90°C for 8 hours;
[0065] Among them, the mass ratio of vinyl triisopropoxy titanate to graphene is 0.05:1; the mass of ethanol is 4 times the mass of graphene.
[0066] Preparation of water-based cutting fluid:
[0067] Prepare the following components by weight: 12 parts of the acrylic copolymer prepared above, 2.5 parts of propylene glycol block polyether Pluronic L62, 13 parts of the vinyl coupling agent modified anti-wear lubricant prepared above, 3 parts of dimethyl dithiocarboxylate, 0.4 parts of 5-chloro-2-methyl-4-isothiazoline-3-one, 18 parts of propylene glycol, and 68 parts of water;
[0068] The above components were stirred at room temperature and a rotation speed of 1600 r / min for 40 minutes to obtain an aqueous cutting fluid.
[0069] Example 3
[0070] Preparation of acrylic acid copolymer:
[0071] Chlorobenzene and azobisisobutyronitrile were added into a reactor, and then acrylic acid and 1-vinyl-3-butylimidazolium bromide were added in a molar ratio of 1:0.35, and then the air in the reactor was replaced by nitrogen for 30 minutes, and then the reaction system was heated to 75°C, reacted for 2.5 hours, cooled to room temperature, and the reaction solution was distilled to remove chlorobenzene to obtain an acrylic acid copolymer;
[0072] The mass of chlorobenzene is 3 times the total mass of acrylic acid and 1-vinyl-3-butylimidazolium bromide; the mass of azobisisobutyronitrile is 0.1wt% of the total mass of acrylic acid and 1-vinyl-3-butylimidazolium bromide.
[0073] Preparation of vinyl coupling agent modified anti-wear lubricant:
[0074] Graphene (KNG-G2 graphene powder purchased from Xiamen Kaina Graphene Technology Co., Ltd.) was mixed with ethanol, and then vinyl triisopropoxy titanate was added to reflux at 60°C for 3 hours, followed by solid-liquid separation and solid phase drying at 90°C for 8 hours;
[0075] Among them, the mass ratio of vinyl triisopropoxy titanate to graphene is 0.05:1; the mass of ethanol is 4 times the mass of graphene.
[0076] Preparation of water-based cutting fluid:
[0077] Prepare the following components by weight: 12 parts of the acrylic copolymer prepared above, 2.5 parts of propylene glycol block polyether Pluronic L62, 13 parts of the vinyl coupling agent modified anti-wear lubricant prepared above, 3 parts of dimethyl dithiocarboxylate, 0.4 parts of 5-chloro-2-methyl-4-isothiazoline-3-one, 18 parts of propylene glycol, and 68 parts of water;
[0078] The above components were stirred at room temperature and a rotation speed of 1600 r / min for 40 minutes to obtain an aqueous cutting fluid.
[0079] Example 4
[0080] Preparation of acrylic acid copolymer:
[0081] Chlorobenzene and azobisisobutyronitrile were added into a reactor, and then acrylic acid and 1-vinyl-3-methylimidazole tetrafluoroborate were added in a molar ratio of 1:0.35, and then the air in the reactor was replaced by nitrogen for 30 minutes, and then the reaction system was heated to 75°C, reacted for 2.5 hours, cooled to room temperature, and the reaction solution was distilled to remove chlorobenzene to obtain an acrylic acid copolymer;
[0082] The mass of chlorobenzene is 3 times the total mass of acrylic acid and 1-vinyl-3-methylimidazolium tetrafluoroborate; the mass of azobisisobutyronitrile is 0.1wt% of the total mass of acrylic acid and 1-vinyl-3-methylimidazolium tetrafluoroborate.
[0083] Preparation of vinyl coupling agent modified anti-wear lubricant:
[0084] Graphene (KNG-G2 graphene powder purchased from Xiamen Kaina Graphene Technology Co., Ltd.) was mixed with ethanol, and then vinyl triisopropoxy titanate was added to reflux at 60°C for 3 hours, followed by solid-liquid separation and solid phase drying at 90°C for 8 hours;
[0085] Among them, the mass ratio of vinyl triisopropoxy titanate to graphene is 0.05:1; the mass of ethanol is 4 times the mass of graphene.
[0086] Preparation of water-based cutting fluid:
[0087] Prepare the following components by weight: 12 parts of the acrylic copolymer prepared above, 2.5 parts of propylene glycol block polyether Pluronic L62, 13 parts of the vinyl coupling agent modified anti-wear lubricant prepared above, 3 parts of dimethyl dithiocarboxylate, 0.4 parts of 5-chloro-2-methyl-4-isothiazoline-3-one, 18 parts of propylene glycol, and 68 parts of water;
[0088] The above components were stirred at room temperature and a rotation speed of 1600 r / min for 40 minutes to obtain an aqueous cutting fluid.
[0089] Example 5
[0090] Preparation of acrylic acid copolymer:
[0091] Chlorobenzene and azobisisobutyronitrile were added into a reactor, and then acrylic acid and 1-vinyl-3-hexyl imidazole tetrafluoroborate were added in a molar ratio of 1:0.35, and then the air in the reactor was replaced by nitrogen for 30 minutes, and then the reaction system was heated to 75°C, reacted for 2.5 hours, cooled to room temperature, and the reaction solution was distilled to remove chlorobenzene to obtain an acrylic acid copolymer;
[0092] The mass of chlorobenzene is 3 times the total mass of acrylic acid and 1-vinyl-3-hexyl imidazolium tetrafluoroborate; the mass of azobisisobutyronitrile is 0.1wt% of the total mass of acrylic acid and 1-vinyl-3-hexyl imidazolium tetrafluoroborate.
[0093] Preparation of vinyl coupling agent modified anti-wear lubricant:
[0094] Graphene (KNG-G2 graphene powder purchased from Xiamen Kaina Graphene Technology Co., Ltd.) was mixed with ethanol, and then vinyl triisopropoxy titanate was added to reflux at 60°C for 3 hours, followed by solid-liquid separation and solid phase drying at 90°C for 8 hours;
[0095] Among them, the mass ratio of vinyl triisopropoxy titanate to graphene is 0.05:1; the mass of ethanol is 4 times the mass of graphene.
[0096] Preparation of water-based cutting fluid:
[0097] Prepare the following components by weight: 12 parts of the acrylic copolymer prepared above, 2.5 parts of sodium dodecyl sulfate, 13 parts of the vinyl coupling agent modified anti-wear lubricant prepared above, 3 parts of dimethyl dithiocarboxylate, 0.4 parts of 5-chloro-2-methyl-4-isothiazoline-3-one, 18 parts of propylene glycol, and 68 parts of water;
[0098] The above components were stirred at room temperature and a rotation speed of 1600 r / min for 40 minutes to obtain an aqueous cutting fluid.
[0099] Example 6
[0100] Preparation of acrylic acid copolymer:
[0101] Chlorobenzene and azobisisobutyronitrile are added into a reactor, and then acrylic acid and 1-vinyl-3-hexyl imidazole tetrafluoroborate are added in a molar ratio of 1:1, and then the air in the reactor is replaced by nitrogen for 30 minutes, and then the reaction system is heated to 75°C, reacted for 2.5 hours, cooled to room temperature, and the reaction liquid is distilled to remove chlorobenzene to obtain an acrylic acid copolymer;
[0102] The mass of chlorobenzene is 3 times the total mass of acrylic acid and 1-vinyl-3-hexyl imidazolium tetrafluoroborate; the mass of azobisisobutyronitrile is 0.1wt% of the total mass of acrylic acid and 1-vinyl-3-hexyl imidazolium tetrafluoroborate.
[0103] Preparation of vinyl coupling agent modified anti-wear lubricant:
[0104] Graphene (KNG-G2 graphene powder purchased from Xiamen Kaina Graphene Technology Co., Ltd.) was mixed with ethanol, and then vinyl triisopropoxy titanate was added to reflux at 60°C for 3 hours, followed by solid-liquid separation and solid phase drying at 90°C for 8 hours;
[0105] Among them, the mass ratio of vinyl triisopropoxy titanate to graphene is 0.05:1; the mass of ethanol is 4 times the mass of graphene.
[0106] Preparation of water-based cutting fluid:
[0107] Prepare the following components by weight: 12 parts of the acrylic copolymer prepared above, 2.5 parts of propylene glycol block polyether Pluronic L62, 13 parts of the vinyl coupling agent modified anti-wear lubricant prepared above, 3 parts of dimethyl dithiocarboxylate, 0.4 parts of 5-chloro-2-methyl-4-isothiazoline-3-one, 18 parts of propylene glycol, and 68 parts of water;
[0108] The above components were stirred at room temperature and a rotation speed of 1600 r / min for 40 minutes to obtain an aqueous cutting fluid.
[0109] Comparative Example 1
[0110] Preparation of acrylic acid homopolymer:
[0111] Chlorobenzene and azobisisobutyronitrile were added into a reactor, and then acrylic acid was added. After that, the air in the reactor was replaced by nitrogen for 30 minutes, the reaction system was heated to 75°C, reacted for 2.5 hours, and then cooled to room temperature. The reaction liquid was distilled to remove chlorobenzene to obtain acrylic acid homopolymer.
[0112] The mass of chlorobenzene is 3 times that of acrylic acid; and the mass of azobisisobutyronitrile is 0.1wt% of that of acrylic acid.
[0113] Preparation of vinyl coupling agent modified anti-wear lubricant:
[0114] Graphene (KNG-G2 graphene powder purchased from Xiamen Kaina Graphene Technology Co., Ltd.) was mixed with ethanol, and then vinyl triisopropoxy titanate was added to reflux at 60°C for 3 hours, followed by solid-liquid separation and solid phase drying at 90°C for 8 hours;
[0115] Among them, the mass ratio of vinyl triisopropoxy titanate to graphene is 0.05:1; the mass of ethanol is 4 times the mass of graphene.
[0116] Preparation of water-based cutting fluid:
[0117] Prepare the following components by weight: 12 parts of the acrylic acid homopolymer prepared above, 2.5 parts of propylene glycol block polyether Pluronic L62, 13 parts of the vinyl coupling agent modified anti-wear lubricant prepared above, 3 parts of dimethyl dithiocarboxylate, 0.4 parts of 5-chloro-2-methyl-4-isothiazoline-3-one, 18 parts of propylene glycol, and 68 parts of water;
[0118] The above components were stirred at room temperature and a rotation speed of 1600 r / min for 40 minutes to obtain an aqueous cutting fluid.
[0119] Comparative Example 2
[0120] Preparation of acrylic acid copolymer:
[0121] Chlorobenzene and azobisisobutyronitrile were added into a reactor, and then acrylic acid and 1-vinyl-3-hexyl imidazole tetrafluoroborate were added in a molar ratio of 1:0.35, and then the air in the reactor was replaced by nitrogen for 30 minutes, and then the reaction system was heated to 75°C, reacted for 2.5 hours, cooled to room temperature, and the reaction solution was distilled to remove chlorobenzene to obtain an acrylic acid copolymer;
[0122] The mass of chlorobenzene is 3 times the total mass of acrylic acid and 1-vinyl-3-hexyl imidazolium tetrafluoroborate; the mass of azobisisobutyronitrile is 0.1wt% of the total mass of acrylic acid and 1-vinyl-3-hexyl imidazolium tetrafluoroborate.
[0123] Preparation of water-based cutting fluid:
[0124] Prepare the following components by weight: 12 parts of the acrylic copolymer prepared above, 2.5 parts of propylene glycol block polyether Pluronic L62, 13 parts of the vinyl coupling agent graphene prepared above (KNG-G2 graphene powder purchased from Xiamen Kaina Graphene Technology Co., Ltd.), 3 parts of dimethyl dithiocarboxylate, 0.4 parts of 5-chloro-2-methyl-4-isothiazoline-3-one, 18 parts of propylene glycol, and 68 parts of water;
[0125] The above components were stirred at room temperature and a rotation speed of 1600 r / min for 40 minutes to obtain an aqueous cutting fluid.
[0126] Performance Testing
[0127] The water-based cutting fluids in the embodiments and comparative examples were tested as follows:
[0128] 1. Rust resistance test: Add cutting fluid to a 500mL wetting tank, heat to 40±2℃, polish the brass test piece, clean it with ethanol, and soak it in a cleaning agent for 10 minutes. Take it out and use filter paper to absorb the liquid at the end and hole of the test piece, hang it vertically on the test piece rack, and then dry the test piece and the rack naturally for 12 hours. Then place the test piece in an environment with a relative humidity of 85% and 85℃ for 12 hours, take it out, dry it, and evaluate the test piece after the test. If there is no obvious change on the surface, it is level 0; if the surface is slightly uneven or loses gloss, it is level 1; if the surface is unevenly discolored, loses gloss, and has spots locally, it is level 2; if the surface is severely discolored or corroded, it is level 3.
[0129] 2. Lubricity test: The maximum no-seizure load (PB value) is tested in accordance with GB / T 3142-2019 standard. The steel ball used is a secondary GCr15 steel ball with a diameter of 12.7 mm and a hardness of 59-61HRC.
[0130] 3. Viscosity change: Measure the viscosity U0 of the water-based cutting fluid at 25°C, then stir it with a high-speed stirrer at 10,000 rpm at 50°C for 30 minutes, continue stirring at 25°C for 1 hour, and then test its viscosity U1. Calculate the viscosity change rate before and after stirring. Viscosity change rate = |U1-U0| / U0*100%.
[0131] The test results are shown in Table 1.
[0132] Table 1 Test results of water-based cutting fluids in the embodiments and comparative examples
[0133] Rust resistance PB / N Viscosity change rate / % Example 1 Level 0 810 3 Example 2 Level 0 803 6 Example 3 Level 1 796 11 Example 4 Level 0 774 63 Example 5 Level 0 652 54 Example 6 Level 0 786 102 Comparative Example 1 Level 2 571 426 Comparative Example 2 Level 1 593 89
[0134] It can be seen from the above test results that the water-based cutting fluid in the present invention not only has excellent lubricity and rust resistance, but also has excellent viscosity shear stability.
[0135] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A water-based cutting fluid composition, measured by weight, characterized in that: The composition contains: 5-20 parts of acrylic copolymer, 1-5 parts of surfactant, 10-25 parts of vinyl coupling agent modified anti-wear lubricant, 1-5 parts of extreme pressure agent, 0.1-2 parts of bactericide, 10-30 parts of polyol solvent and 40-80 parts of water.
2. The composition according to claim 1, characterized in that The acrylic copolymer contains a structural unit A provided by acrylic acid and a structural unit B provided by a vinyl imidazole compound represented by formula (I). In formula (I), R1 is selected from C1-C12 alkyl, X - It is an anion.
3. The composition according to claim 2, characterized in that In formula (I), X - It is tetrafluoroborate ion, iodide ion, bromide ion or acid radical ion; the molar ratio of the structural unit A to the structural unit B is 1:(0.1-1).
4. The composition according to claim 1, characterized in that The surfactant is selected from nonionic surfactants.
5. The composition according to claim 4, characterized in that The nonionic surfactant is at least one selected from propylene glycol block polyether Pluronic L31, propylene glycol block polyether Pluronic L35, propylene glycol block polyether Pluronic L61, propylene glycol block polyether Pluronic L62, propylene glycol block polyether Pluronic L64 and propylene glycol block polyether Pluronic L81.
6. The composition according to claim 1, characterized in that The preparation method of the vinyl coupling agent modified anti-wear lubricant comprises: mixing graphene with ethanol, then adding the vinyl coupling agent for reflux reaction, and then performing solid-liquid separation and solid-phase drying.
7. The composition according to claim 6, characterized in that The vinyl coupling agent is selected from vinyl triisopropoxy titanate and / or vinyl tri(dioctyl pyrophosphate) titanate; the mass ratio of the vinyl coupling agent to graphene is (0.04-0.06):1; the conditions of the reflux reaction include: a temperature of 50-70°C and a time of 2-4 hours.
8. The composition according to claim 1, characterized in that The extreme pressure agent is selected from sulfurized fatty acid esters and / or phosphate compounds.
9. The composition according to claim 1, characterized in that The bactericide is selected from isothiazolinone compounds; the polyol solvent is selected from at least one of ethylene glycol, diethylene glycol, propylene glycol, 1,3-propylene glycol, 1,4-butanediol and 1,2-butanediol.
10. A water-based cutting fluid, characterized in that: The aqueous cutting fluid contains the aqueous cutting fluid composition according to any one of claims 1 to 9.